Lenalidomide monotherapy in heavily pretreated patients with non-Hodgkin lymphoma: an Italian observational multicenter retrospective study in daily clinical practice. Issue 6 (June 2015) - Zinzani, Pier Luigi; Rigacci, Luigi; Cox, Maria Cristina; Devizzi, Liliana; Fabbri, Alberto; Zaccaria, Alfonso; Zaja, Francesco; Di Rocco, Alice; Rossi, Giuseppe; Storti, Sergio; Fattori, Pier Paolo; Argnani, Lisa; et al.
Abstract Clinical trial results indicate that lenalidomide, an immunomodulatory drug, is a promising treatment in relapsed/refractory non-Hodgkin lymphoma (NHL). This retrospective multicenter study was conducted in patients with relapsed/refractory NHL treated with lenalidomide monotherapy through a Named Patient Program in Italy. Principal endpoints were overall response rate (ORR), safety and overall survival (OS). The ORR in 64 evaluable patients was 42.2% and was similar among patients receiving 10, 15 or 25 mg/day lenalidomide. Response rates in patients with mantle cell, diffuse large B-cell and follicular lymphoma were 45.5%, 42.1% and 20%, respectively. Among patients who responded to most recent prior therapy, ORR was 50.0% versus 36.8% in patients with refractory NHL. Mean duration of response in patients receiving any lenalidomide dose was 10.5 months; 1-year progression-free survival and OS were 50.3% and 82.6%, respectively. These findings suggest that lenalidomide is effective and safe for heavily pretreated patients with NHL in the clinical setting.